2015
DOI: 10.14283/jarcp.2015.67
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake of Minerals and Prostate Cancer: Insights Into Problem Based on the Chemical Element Contents in the Prostate Gland

Abstract: Objective: As men age total dietary mineral bioavailability falls which may increase the risk of prostate cancer. The aims of this study were to investigate the changes in main mineral contents in prostate gland that occurred with aging. Design: Population based study on changes in mineral contents in prostate gland with ageing. Participants and setting: 65 free-living healthy men aged 21-87 years who had died suddenly. Prostates were removed at necropsy and the samples of morphologic normal prostate tissue we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…In the both OM and ES tissue the mean Se mass fractions were more than 10 times higher than in normal bone (Table 3). A high Se level was reported in malignant tumors of the ovary [58], lung [59], prostate [60][61][62][63][64][65][66][67][68], breast [69,70], gastro intestinal tract [71], and also in cancers of the stomach [72] and thyroid [73]. Moreover, in our previous study elevated levels of Se were found in such malignant tumors of bone as osteogenic sarcoma [74], chondrosarcoma [75], and malignant giant cell tumor of bone [76].…”
Section: Seleniummentioning
confidence: 94%
See 1 more Smart Citation
“…In the both OM and ES tissue the mean Se mass fractions were more than 10 times higher than in normal bone (Table 3). A high Se level was reported in malignant tumors of the ovary [58], lung [59], prostate [60][61][62][63][64][65][66][67][68], breast [69,70], gastro intestinal tract [71], and also in cancers of the stomach [72] and thyroid [73]. Moreover, in our previous study elevated levels of Se were found in such malignant tumors of bone as osteogenic sarcoma [74], chondrosarcoma [75], and malignant giant cell tumor of bone [76].…”
Section: Seleniummentioning
confidence: 94%
“…A low level of Zn was reported in malignant tumors of liver [78,79,80], kidney [78], uterus [81], lung [80,82], prostate [60][61][62][63][64][65][66][67]80,[83][84][85][86], stomach [87], testis [87], thyroid [72,80,86,87] and in esophageal squamous cell cancer [88]. These facts imply that reduced Zn content in tumors is probably one of the factors in the etiology of malignant transformation of different tissues, because Zn deficiency has been linked to severe deficiency in immune function and disruption in T-Cell function.…”
Section: Zincmentioning
confidence: 99%
“…The latter might be evidenced by biochemical research, and these minerals include Mg, Se, Mn, B, Ca, Zn, Co, Cr, and Fe. [12,13] According to recent studies, heavy metals are important components in human blood, and they should be employed as biomarkers to diagnose a variety of disorders, including cancer. [14].…”
Section: Introductionmentioning
confidence: 99%